Click chemistry‐based synthesis and cytotoxic activity evaluation of 4α‐triazole acetate podophyllotoxin derivatives. (28th November 2018) - Hou, Wei; Zhang, Guanjun; Luo, Zhi; Su, Lin; Xu, Hongtao
Abstract: A series of novel 4α‐triazole acetate podophyllotoxin derivatives were synthesized via click chemistry. In vitro cytotoxic activity evaluation showed that most of the derivatives exhibited potent inhibitory activities against the tested cancer cell lines with low nanomolar IC50 values. Further studies demonstrated that compound31 exhibited broad‐spectrum cytotoxic activities, effectively overcame drug‐resistance, and showed relatively weak cytotoxicity on non‐cancer cells. Preliminary mechanistic studies indicated that31 might have action on microtubule, cause cell cycle arrest at G2 /M phase, and induce apoptosis in human PC‐3 cancer cells. Abstract : Low nanomolar IC50 values. Effective against drug‐resistance. G2 /M phase arrest and apoptosis.